Urban heritage conservation through redevelopment strategies: a case study of Kuala Lumpur - Wan Abdullah Zawawi, Noor Amila; Abdullah, Alias (Centre for the Study of Architecture in the Arab Region (CSAAR) Press, 2008)
Towns in Malaysia are rich in built heritage from colonial days and the symbiotic existence of Chinese and Malays, which dominated urban areas. The nostalgic combination of old and new quaintly describes our towns. On the other hand, pressure for redevelopment is increasing in the face of fast-changing, ominously globalizing world today to create a global image for a city centre. However, as shown by vast literature, the success of global cities relies increasingly on the distinctiveness of place than on faceless city. Thus it becomes critical to find a balance between conservation and redevelopment in order to preserve identity. This paper addresses redevelopment of old inner-city areas through adaptive reuse of traditional shophouses in Kuala Lumpur, Malaysia. Conservation is undoubtedly possible through redevelopment. Using the case study of the city centre of Kuala Lumpur, we examine the public policies as an instrument to redevelopment within the context of conservation. We look at the roles played by local government in conservation in relation to these development policies. The findings suggest that various development policies partake in conservation of urban heritage, despite great demands for total redevelopment. Designated policies to conservation, on the other hand, have yet to prove their efficacy, including the latest heritage act.